Nghiên cứu tổng hợp thuốc trừ sâu thế hệ mới, thân thiện với môi trường Etofenprox - Hoằng và cộng sự, Đào Văn (Vietnam Journal of Chemistry, 2014)
Etofenprox, a new environmental friendly pyrethroid insecticide is successfully used in Vietnam. Several syntheses have been reported. Here, we wish to report a short and convenient synthesis of Etofenprox by condensation of 2-(4-ethoxyphenyl)-2-methylpropyl alcohol with 3-phenoxybenzyl chloride, utilizing base and transphase catalysis n-Bu4NBr, in acetonitryl as solvent. The EC and EW formulations insecticidal activity of the obtained product was tested in laboratory against some common insect pests and mosquitoes.